Identification of seed storage protein markers for drought tolerance in mungbean - Tripathy, Swapan Kumar; Mohanty, Priyadarshini; Jena, Monalisha; Dash, Sasmita; Lenka, Devraj; Mishra, Dayanidhi; Nayak, Pramod Kumar; Swain, Digbijaya; Ranjan, Rajesh; Pradhan, Kedareswar; Senapati, Niranjan; Mohapatra, Pavitra Mohan; et al. (Research in Biotechnology, 2016)
A set of 292 mungbean germplasm accessions including 62 popularly adapted local land races and two wild forms (Vigna radiata var. sublobata), important breeding lines and standard ruling varieties were screened for drought stress tolerance at seedling stage. Eight genotypes e.g., C. No. 35, OUM 14-1, OUM 49-2, Pusa 9072, OM 99-3, Banapur local B, Nipania munga, Kalamunga 1-A) have been identified to possess drought tolerance. Globulin seed storage protein profiling was carried out in 19 selected mungbean genotypes comprising eight drought tolerant, seven drought sensitive, two wild forms of mungbean (TCR 20 and TCR 213) and two standard checks (LGG 460 and T 2-1) to explore differentially expressed polypeptides. Seed protein profiles revealed 15 scorable polypeptide bands with molecular weights ranging from 10.0 to 102.2kD. A specific 12.8kD polypeptide band was present in all above drought tolerant test genotypes including the wild accession TCR 20. Such a polypeptide band may serve as useful biochemical marker for identification of drought tolerant genotypes in mungbean. Key words: Genetic diversity, seed storage protein profile, wild and cultivated Vigna radiata.